2016
DOI: 10.1101/084624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The natural selection of metabolism and mass selects allometric transitions from prokaryotes to mammals

Abstract: Inter-specific body mass allometries can evolve from the natural selection of mass, with ±1/4 and ±3/4 exponents following from the geometry of intra-specific interactions when density dependent foraging occurs in two spatial dimensions (2D, Witting 1995). The corresponding values for three dimensional interactions (3D) are ±1/6 and ±5/6.But the allometric exponents in mobile organisms are more diverse than the prediction. The exponent for mass specific metabolism tends to cluster around -1/4 and -1/6 in terre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(79 citation statements)
references
References 117 publications
1
78
0
Order By: Relevance
“…The development of such a theory is the aim of this article. To approach the goal, I use the framework of Malthusian relativity (MR, see Witting, 1997Witting, , 2008Witting, , 2017 to deduce a natural selection that is sufficient to explain the metabolism, body masses, major life-history transitions, and interspecific allometries that are observed within and across lifeforms from viruses over prokaryotes and larger unicells to multicellular animals. The proposed selection describes how mobile lifeforms with elevated metabolic rates, large body masses, and reduced sexual reproduction are selected as a deterministic consequence of the origin of replicating molecules.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of such a theory is the aim of this article. To approach the goal, I use the framework of Malthusian relativity (MR, see Witting, 1997Witting, , 2008Witting, , 2017 to deduce a natural selection that is sufficient to explain the metabolism, body masses, major life-history transitions, and interspecific allometries that are observed within and across lifeforms from viruses over prokaryotes and larger unicells to multicellular animals. The proposed selection describes how mobile lifeforms with elevated metabolic rates, large body masses, and reduced sexual reproduction are selected as a deterministic consequence of the origin of replicating molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The primary selection of metabolism was recently incorporated into the feed-back selection of MR in relation to the evolution of interspecific allometries (Witting, 2017). This showed that massspecific metabolism can be selected as a proxy for the pace of the resource handling that generates net energy for self-replication.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations